CATALOGUE OF COORDINATES AND B-MAGNITUDES IN - 20є – +2є ZONE BASED ON THE ULUGH BEG ASTRONOMICAL INSTITUTE PART OF THE FON PROJECT - Yuldoshev, Q. H.; Muminov, M. M.; Ehgamberdiev, Sh. A.; Relke, H.; Protsyuk, Yu. I.; Kovylianska, O. E.; Protsyuk, S. V.; Andruk, V. M. (Одеські астрономічні публікації, 2017)
Catalogue of 13.4 million stars down to 17.5m was obtained in 2017 by using plates from the Kitab Observatory of Ulugh Beg Astronomical Institute (UBAI) of the Uzbek Academy of Sciences. Kitab’s part of Photographic Sky Survey (Russian abbreviation is FON, in next contexts) project include more than 2600 photographic plates, exposed on the Double Astrograph of Zeiss (DAZ, D/F = 40/300, 69"/mm) from 1981 to 1996. Digitizationof these plates was made by using Epson Expression 10000XL scanner with the 1200 dpi resolution. Catalogue includes objects from the 1963 plates in declination zone between -20° and +2° for middle epoch 1984.97. The equatorial coordinates of objects were determined in the Tycho-2 reference system and the B-magnitudes in the system of the photoelectric standards. Five participants from Uzbekistan, Germany and Ukraine have taken part in the processing of the digitized images. The average internal accuracy of the catalogue for one observation are 0.23" and 0.15m for the equatorial coordinates and B-magnitudes respectively. For the stars brighter than 14m the errors are 0.09" and 0.05m respectively. The analysis of the catalogue and its comparison with the several astrometric catalogues was done.